Testing the multi-factor asset pricing model in the Iraqi Stock Exchange - Ahmed Fares, Ali; Muhammad Ayoub, Saja (Iraqi Journal for Administrative Sciences, 2024)
This study aims to test the effect of the variables of the French Fama model-with the five factors,on the required return on shares in the Iraqi stock market.Operational profitability premium(RMW)and investment premium(CMA)as independent variables,and in order to test the model, it was applied to the study sample,which was represented by(33)companies out of (130) companies listed on the Iraq Stock Exchange for the period from July2006to June 2021,and to achieve the goal of The study and its main hypothesis were tested.The multiple regression model was used through the Excel-v16program.Accordingly,the study concluded a number of conclusions, perhaps the most important of which are:There is a significant effect of the multi-factor asset pricing model on the required rate of return on shares, and the study came up with a number of recommendations,the most important of which are:The importance of investing in small-sized companies,because they achieve higher rates of return than in large companies.